Contrasting genetic association of IL2RA with SLE and ANCA - associated vasculitis - Todd John A; Lowe Christopher E; Clatworthy Menna R; Carr Edward J; Wong Andrew; Vyse Timothy J; Kamesh Lavanya; Watts Richard A; Lyons Paul A; Smith Kenneth GC (BMC, 2009)
Abstract Background Autoimmune diseases are complex and have genetic and environmental susceptibility factors. The objective was to test the genetic association of systemic lupus erythematosus (SLE) and anti-neutrophil cytoplasmic antibody (ANCA) - associated systemic vasculitis (AAV) with SNPs in the IL2RA region and to correlate genotype with serum levels of IL-2RA. Methods Using a cohort of over 700 AAV patients, two SLE case-control studies and an SLE trio collection (totalling over 1000 SLE patients), and a TaqMan genotyping approach, we tested 3 SNPs in the IL2RA locus, rs11594656, rs2104286 & rs41295061, each with a prior association with autoimmune disease; rs11594656 and rs41295061 with type 1 diabetes (T1D) and rs2104286 with multiple sclerosis (MS) and T1D. Results We show that SLE is associated with rs11594656 (P = 3.87 × 10-7) and there is some evidence of association of rs41295061 with AAV (P = 0.0122), which both have prior association with T1D. rs2104286, an MS and T1D - associated SNP in the IL2RA locus, is not associated with either SLE or AAV. Conclusion We have confirmed a previous suggestion that the IL2RA locus is associated with SLE and showed some evidence of association with AAV. Soluble IL-2RA concentrations correlate with rs11594656 genotype in quiescent disease in both AAV and SLE. Differential association of autoimmune diseases and SNPs within the IL2RA locus suggests that the IL2RA pathway may prove to play differing, as yet undefined, roles in each disease.